Maternal and Perinatal Outcome of Triplet Pregnancies in a Tertiary Care Hospital in North India: A Prospective Observational Study - Sabreen Wani; Fiza Amin; Shagufta Yasmeen Rather (The Journal of Medicine, Law & Public Health)
Background:  The purpose of this study was to identify the present trends in maternal, foetal, and perinatal outcomes and complications associated with triplet pregnancy at a tertiary referral hospital in India.